Collective bargaining structure in Northern Ireland - dimensions, determinants and development - Black, Boyd (Statistical and Social Inquiry Society of Ireland, 1985)
Up to 1920, industrial relations developed in Ireland within the constitutional framework of the Act of Union 1801 as part of the British system, with the same laws and broadly the same institutional arrangements. Then, under the Government of Ireland Act 1920, legislative and executive responsibility for industrial relations in Northern Ireland was devolved to the Northern Ireland Parliament at Stormont, along with other non reserved matters.
Read before the Society, 7 May 1985
Keywords: Industrial relations; Collective bargaining; 314.15